أدوات التنمية المائية المستدامة في الجزائر - الحمزة, عبد الحليم (جامعة الوادي - University of Eloued, 2023)
تهدف هذه الدراسة الى إبراز مدى التقدم في تطبيق أدوات التنمية المائية المستدامة في الجزائر، من خلال إبراز واقع التقدم في تهيئة البيئة المواتية وكذلك الأدوات الإدارية للتنمية المائية المستدامة، وتوصلت الدراسة الى ان الجزائر وضعت سياسات وخطط جديدة خاصة بالمياه تهدف إلى اعتماد أسلوب جديد لإدارة قطاع الموارد المائية وفق مبادئ الاستدامة، إلا أن الجزائر تعرف تأخرا في تطبيق الأدوات الإدارية للتنمية المائية المستدامة. This study aims to highlight the extent of progress in application of sustainable water development tools in Algeria, by highlighting reality of progress in creating a favorable environment as well as administrative tools for sustainable water development. The study concluded that Algeria has developed new water policies and plans aimed at adopting a new method for managing the water resources sector in accordance with the principles of sustainability. However, Algeria knows a delay in the application of administrative tools for sustainable water development
Tools for sustainable water development in Algeria
مقال
Keywords: السياسة المائية؛ التنمية المائية المستدامة؛ الأدوات الإدارية؛ الجزائر.